2022
DOI: 10.1002/anie.202214267
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Latency of Hydrosilylation Catalyst by Ligand Density on Nanoparticle Supports

Abstract: Functionalizing inorganic particles with organic ligands is a common technique for heterogenizing organometallic catalysts. We describe how coordinating molecular platinum to silica nanoparticles functionalized with a high density of norbornene ligands causes unexpected latency of the catalytic activity in hydrosilylation reactions when compared to an identical reaction in which the norbornene is not tethered (2 % vs 97 % conversion in 1 h). Performing the hydrosilylation at elevated temperature (70 °C) suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Alternatively, we propose that latency in FROMP resins can be achieved via a localized separation between monomer and active catalyst that can be removed upon exposure to an external stimulusa technique ubiquitous in biological systems. , An established way to delay contact between reactive pairs is the encapsulation of molecular cargo in the form of polymer microparticles (PMPs). This well-studied method has been applied to the controlled release of drug molecules, , catalyst species, and polymerization initiators. Pojman et al demonstrated that microencapsulation of organic peroxide initiators increases the storage life of free-radical acrylate FP . Extended storage times (>1 day) resulted in significant decreases in the mechanical properties of the polymer products and SP still occurred within a two month period.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, we propose that latency in FROMP resins can be achieved via a localized separation between monomer and active catalyst that can be removed upon exposure to an external stimulusa technique ubiquitous in biological systems. , An established way to delay contact between reactive pairs is the encapsulation of molecular cargo in the form of polymer microparticles (PMPs). This well-studied method has been applied to the controlled release of drug molecules, , catalyst species, and polymerization initiators. Pojman et al demonstrated that microencapsulation of organic peroxide initiators increases the storage life of free-radical acrylate FP . Extended storage times (>1 day) resulted in significant decreases in the mechanical properties of the polymer products and SP still occurred within a two month period.…”
Section: Introductionmentioning
confidence: 99%